Analisis dan Perancangan E-CRM Pada Perusahaan Advertising - Hendarti, Henny; Suryanto, Suryanto; Septianto, Otto Fikri (Bina Nusantara University, 2010)
The purpose of this study was to analyze the needs and customer satisfaction in service advertising and design an attractive site customer satisfaction, user friendly and dynamic. Ways to do research using analytical method, data collection method, and design method. The collection of data and information were done through a field research. The results obtained from this research is the design of e-CRM applications (Electronic Customer Relationship Management) which aims to produce an interactive Internet-based applications for any strategy to enhance relationships with existing customers, increase new customers and increase profits from the sale. In addition, companies can thrive in providing quality service to our customers, which in turn can increase its profit. The conclusion of this research is to create a dynamic website, which is useful for providing better services to consumers, thus increasing profits for customers and companies.